Good Corporate Governance dan Kinerja Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Tahun 2005-2013 - Christian Meichael Renaldo Situmorang; I Made Sudana (Jurnal Manajemen dan Bisnis Indonesia, 2015)
This study aims to determine the effect of good corporate governance on corporate’s financial performance and market value. Comprehensively, the influence of good corporate governance is proxied by corporate governance perception index and partially are proxied by the quality of information disclosure, independent commisioner, board size, remuneration and nomination committee, institutional ownership, and managerial ownership. The company's financial performance is proxied by the return on assets and market value is proxied by Tobins'q. The study also use other variables, they are firm size, economic conditions, and leverage. The sample used in this study is a non-financial state-owned enterprises that is listed on the Indonesia Stock Exchange in the year of 2005 to 2013The analysis technique used is multiple linear regression. Corporate governance perception index has an unsignificant positive effect on the firm’s financial performance and market value. The quality of information disclosure, institutional ownership, and managerial ownership have a significant positive effect on firm’s performane. Board size, remuneration and nomination committee, company size, and economi conditions have an unsignificant positive effect on the firm’s financial performance and market value, while independent commisioner and leverage have an unsignficant negative impact on the firm’s financial performance and market value. Keywords: good corporate governance, corporate governance perception index, return on assets, Tobins’q